1. Diversity of Parasites on the Garing Fish (Tor tambroides) in Jorong Ikan Banyak River, Gunuang Omeh Subdistrict, Lima Puluh Kota Regency, West Sumatera Province - Zulhamezi Nofila; Yudha Fahrimal; Razali Daud (Universitas Syiah Kuala, 2020)
The study aims to determine diversity of parasites that infect garing fish and determine their prevalence. A total of 50 garing fish samples were taken from three places, 17 fishes from the forbidden pool of Lubuk Sati, 16 fishes from the forbidden pool of Batu Subalah and 17 fishes from the forbidden pool of Lubuk Pinang along the Jorong Ikan Banyak River, Gunuang Omeh Subdistricts, Lima Puluh Kota Regency West Sumatra Province. Garing fish sample were examined in the parasitology laboratory of Bukittinggi Veterinary institute for examination of ectoparasites and endoparasites, using the natif method. The result research found that five ectoparasites that infect the garing fish is Dactylogyrus sp. was found on the gills with 38.1% prevalence, Gyrodactylus sp. was found in fins and mucus with a prevalence of 14%, Ichtyopthirius multifiliis was found in gill, mucus and fins with 36.7% prevalence, Trichodina sp. was found in the fins and mucus with a prevalence of 5.9%, Argulus sp. found on fins and mucus with a prevalence of 7.% and there are two endoparasites that infect the garing fish they are Camallanus sp. in the intestine with a prevalence of 7.9% and Capillaria sp. in intestine with prevalence of 10.1%.